Intellectual property rights protection and export diversification: The application of utility model laws - Kimm Gnangnon; Constance Besse Moser (World Trade Organization (WTO), 2014)
We examine in this paper the impact of the tightening of IPRs, notably patents rights, and the adoption of utility model laws on export diversification. To perform our analysis, we used panel data covering 89 developing and developed countries (of which 55 developing countries) over the period 1975 - 2003, and Lewbel (2012)'s instrumental variable technique. Our results lead us to conclude that for developing countries, legal protection for minor and adaptive inventions could be a springboard for further strengthening of IPRs protection in spurring export diversification, which is essential for the structural change needed for their economic development.
Keywords: F14; O24; O34; 330; Intellectual Property Rights; Utility Model Laws; Export Diversification; Lewbel Instrumental Variable Technique